Reaksi Pasar Terhadap Peristiwa Covid-19 pada Perusahaan Hotel, Restoran, dan Pariwisata yang Terdaftar di Bursa Efek Indonesia - Dinesya Winarto; Juniarti Juniarti (Business Accounting Review, 2021)
The emergence of the Covid-19 case in Indonesia for the first time on March 2, 2020, hinderedcommunity activities, including travel. Then to prevent the increasingly boundless spread of the virus, thegovernment implemented Large-Scale Social Restrictions (PSBB) in Indonesia for the first time on April 10,2020. With this PSBB, community activities were even more restricted. Finally, in early 2021 the vaccinecould be given to the community, and it is hoped that it will restore community activities and the Indonesianeconomy. Therefore, this study aims to determine how investors respond to these three periods of events.Investor response was measured using Cumulative Abnormal Return (CAR) with an event window [-5, 0, +5],and Covid-19 events were measured using a dummy variable. The sample of this research is the hotel,restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange. The findings of thisstudy are that Covid-19 had an insignificant negative effect on investor responses during the first case event.Then, in the first PSBB event period, Covid-19 had a significant favourable influence on investor response.Moreover, in the period of the first vaccine event, Covid-19 had an insignificant positive effect on investorresponse. The control variables in this study were ROA, EPS, and CFO. ROA had an insignificant negativeeffect in the first case event and a significant positive effect on the period of the first PSBB event and the firstvaccine. EPS had no significant positive effect on the three event periods. CFO had a significant adverse effecton the three event periods.